The Development of Learning Model of Problem Confirmation with Elaborative And Collaborative Sharing (PCECS) Associated with Mind Mapping Approach - Ichwan Triantono; Joko Waluyo; Iis Nur Aisyah (Green Publisher Indonesia, 2022)
The objective of this research was to develop a learning model of problem confirmation with elaborative and collaborative sharing associated with mind mapping approach [PCECS] to foster the students’ critical thinking skills in science learning at secondary high school. This research used the research and development approach by using validation instrument of need assessment via google form. 10 teachers of 9 schools in Jember Regency were taken as the respondents. The validation results referred to what the teachers Idea, in which critical thinking skills and prior knowledge were 55,6% intertwined. On the other hand, 90% of teachers agreed upon the underdeveloped students’ critical thinking skills. It was found in the validation results that there need a development on learning model to maximize the prior knowledge as one of the factors to foster critical thinking skills and learning achievement.